Magnetic resonance-determined sodium removal from tissue stores in hemodialysis patients - Dahlmann, Anke; Dörfelt, Kathrin; Eicher, Florian; Linz, Peter; Kopp, Christoph; Mössinger, Irina; Horn, Stephan; Bueschges-Seraphin, Beatrix; Wabel, Peter; Hammon, Matthias; Eckardt, Kai-Uwe; Kotanko, Peter; et al. (Kidney International, 2015)
We have previously reported that sodium is stored in skin and muscle. The amounts stored in hemodialysis (HD) patients are unknown. We determined whether (23)Na magnetic resonance imaging (sodium-MRI) allows assessment of tissue sodium and its removal in 24 HD patients and 27 age-matched healthy controls. We also studied 20 HD patients before and shortly after HD with a batch dialysis system with direct measurement of sodium in dialysate and ultrafiltrate. Age was associated with higher tissue sodium content in controls. This increase was paralleled by an age-dependent decrease of circulating levels of vascular endothelial growth factor-C (VEGF-C). Older (>60 years) HD patients showed increased sodium and water in skin and muscle and lower VEGF-C levels compared with age-matched controls. After HD, patients with low VEGF-C levels had significantly higher skin sodium content compared with patients with high VEGF-C levels (low VEGF-C: 2.3 ng/ml and skin sodium: 24.3 mmol/l; high VEGF-C: 4.1 ng/ml and skin sodium: 18.2 mmol/l). Thus, sodium-MRI quantitatively detects sodium stored in skin and muscle in humans and allows studying sodium storage reduction in ESRD patients. Age and VEGF-C-related local tissue-specific clearance mechanisms may determine the efficacy of tissue sodium removal with HD. Prospective trials on the relationship between tissue sodium content and hard end points could provide new insights into sodium homeostasis, and clarify whether increased sodium storage is a cardiovascular risk factor.
EVALuna2:3717